The Complication of Tinea Pedis to Onychomycosis On Disposal Officer - Ahmad Ghiffari; Mitayani Purwoko; Reza Reza; Dewi Yuniasih; Lucille Anisa Suardin; Indri Ramayanti (Universitas Ahmad Dahlan, 2023)
Superficial dermatomycosis is the most common type of infection, which affects 20-25% of the world's population. Tinea pedis can cause onychomycosis and has been associated with onychomycosis in 30 to 50% of cases. The study aimed to determine the relationship between Tinea pedis and the occurrence of onychomycosis in scavengers. The research design used in this study is cross-sectional. The sample used was scavengers at the Sukawinatan landfill in Palembang. The sampling method used a consecutive sampling technique for as many as 70 respondents. This study used data obtained from interviews and examination of skin scrapings under a microscope and fungal culture. The results obtained were 31 respondents (44.3%) with tinea pedis and 39 respondents (55.7%) who did not have tinea pedis. Fifty-five respondents (78.5%) had onychomycosis, while 15 (21%) did not. Tinea pedis and onychomycosis are strongly related. The Odds Ratio (95%=CI) of the Chi-Square test was 0.309. Tinea pedis is 0.309 times more likely to have onychomycosis. In conclusion, there was a significant relationship between tinea pedis and the occurrence of onychomycosis in the disposal officer. The emergence of tinea pedis is due to the daily life of scavengers who live side by side with garbage and the lack of concern for personal hygiene which is not optimal, can be prevented and treated.